Leadership positioning among U.S. firms investing in China. Issue 1 (February 2016) - Wooster, Rossitza B.; Paul, Donna L.
Highlights: We investigate industry leadership by U.S. firms investing in China (1980–2005). We develop hypotheses using the awareness, motivation, and capability paradigm. Results: leaders have greater multinational experience and market orientation. Leader firms also have higher input cost structure and smaller scale of operations. Provincial characteristics influence both entry timing and mode of entry decisions. Abstract: This study investigates leadership positioning by U.S. firms in China using the awareness, motivation, capability (AMC) perspective. We define leadership as first in industry to invest in China, and find that leaders have characteristics associated with higher AMC, evidenced by pre-existing multinational experience, higher product market orientation, smaller scale of operations, and higher input cost structure. Notably, the motivation to lower input costs and the prior capability in multinational operations mattered only for the first wave of firms leading industry investment earlier in time, while firms with smaller scale of operations exhibited a preference to lead investment in less popular provinces. Overall, these results provide a unique view on how AMC characteristics influence international investment decisions, suggesting that firms both strategically lead and strategically follow. In additional analysis, we examine how leaders and followers positioned themselves with respect to ownership, and find that leaders were more likely to choose entry modes that offered ownership control over flexibility, consistent with internalization theories.